The Influence of Bridge Maintenance Strategies to Extend Service Life in Civil Engineering: A Meta-Analysis Study - Krisdiyanto, Aris; Dewi, Kemmala; Santosa, Tomi Apra (Research and Social Study Institute, 2024)
Pemeliharaan jembatan merupakan elemen krusial dalam manajemen infrastruktur teknik sipil untuk memastikan keberlanjutan fungsi struktural dan keselamatan pengguna. Penelitian ini bertujuan untuk menganalisis secara meta-analitis pengaruh berbagai strategi pemeliharaan jembatan terhadap perpanjangan umur layanannya. Data diambil dari 15 studi yang mencakup strategi pemeliharaan preventif, prediktif, korektif, hingga rehabilitasi penuh, serta penggunaannya pada jembatan dengan beragam kondisi lingkungan dan material. Hasil meta-analisis menunjukkan bahwa strategi pemeliharaan jembatan memiliki pengaruh signifikan terhadap perpanjangan umur layanannya dengan nilai ( d= 0.825 ; p < 0.001) kategori effect size yang tinggi. Temuan ini memberikan informasi penting dalam pemeliharaan jembatan dalam teknik sipil. Bridge maintenance is a crucial element in civil engineering infrastructure management to ensure the sustainability of structural functions and user safety. This study aims to conduct a meta-analytical analysis of the impact of various bridge maintenance strategies on extending their service life. Data were collected from 15 studies covering preventive, predictive, corrective maintenance strategies, and full rehabilitation, as well as their application to bridges with diverse environmental conditions and materials. The results of the meta-analysis indicate that bridge maintenance strategies have a significant impact on extending their service life, with a high effect size (d = 0.825; p < 0.001). These findings provide important insights into bridge maintenance in civil engineering.